Предмет: Алгебра,
автор: lisovarseniy
Подскажите пожалуйста как мы получили такой знаменатель?
Приложения:
Ответы
Автор ответа:
0
Упрощение
Решим уравнение:
x3 – 3x + 2 = 0
х1 = 1
x3 – 3x + 2 Ix - 1
-(x3 – x2) x2 + x - 2
x2 – 3x
-(x2 – x)
- 2x + 2
-(-2x + 2)
0 x3 – 3x + 2 = (x – 1)( x2 + x – 2) x2 + x – 2 = 0 х2 = - 2 х3 = 1 x3 – 3x + 2 = (x – 1)2( х + 2)
-(x3 – x2) x2 + x - 2
x2 – 3x
-(x2 – x)
- 2x + 2
-(-2x + 2)
0 x3 – 3x + 2 = (x – 1)( x2 + x – 2) x2 + x – 2 = 0 х2 = - 2 х3 = 1 x3 – 3x + 2 = (x – 1)2( х + 2)
Приложения:
Похожие вопросы
Предмет: История,
автор: zanasylkurman
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Русский язык,
автор: vanyaearoplay
Предмет: Математика,
автор: юленька50
Предмет: Химия,
автор: alieva20131